Instytucjonalizm i jego znaczenie w analizie różnorodności form aktywności gospodarczej i zróżnicowania gospodarek kapitalistycznych - Murawiak, Katarzyna (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The literature on economic development pays lot of attention to the success of Asian economies. Much of the interest arises from the awareness that these economies are built on different organizational frameworks than economies from the West countries. At macroeconomic level, conditions in the world market have been identified as factors prompting new types of organizational forms. Trying to understand complexity of economic activity, some researchers refer to network theory and perspective on capitalism – its social and differentiated character. Such an outlook deviates from the view that sees the “end of history” of western liberal capitalism. Economies, rather than converging, exhibit many varieties of capitalism, with much of the difference arising from the way in which business relates to one another, and from the cultural and institutional context. Traditionally, economists have tended to exclude social and cultural factors from their analyses. However, the economic process is also a socio-cultural process, and institutions are central to the socio-cultural construction of the economic activity. This article expands network theory with its macro background, by analyzing the approaches to institutionalism, and claims that form and evolution of the economic landscape cannot be fully understood without giving due attention to the various social institutions, on which economic activity depends, and through with it is being shaped
Keywords: institutionalism; institutions; evolution; embeddedness; capitalism; network